Foods and dietary supplements in the prevention and treatment of disease in older adults - Watson, Ronald R. (Ronald Ross) (Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)
This book brings together a broad range of experts working on the different aspects of foods and dietary supplements (vitamins, herbs, plant extracts, etc.) in health promotion and disease prevention. They have contributed chapters which define a range of ways in which foods, nutriceuticals, and dietary supplements prevent disease and promote health in older adults. They begin by reviewing the medicinal role of foods, herbal, and dietary supplements in health promotion in older adults, as well as some of the most commonly used supplements in elder "self-medication